2022
DOI: 10.1002/rth2.12782
|View full text |Cite
|
Sign up to set email alerts
|

Untreated bleeds in people with hemophilia A in a noninterventional study and intrapatient comparison after initiating emicizumab in HAVEN 1–3

Abstract: Background Bleeding in people with hemophilia A can be life threatening, and intra‐articular bleeds can result in joint damage. Most clinical studies focus on treated bleeds, while bleeds not treated with coagulation factor(s) (untreated bleeds) are underreported. Objectives We assessed the incidence of untreated bleeds during a noninterventional study (NIS) wherein people with hemophilia A, with or without factor VIII (FVIII) inhibitors, were managed according to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This may reflect concerns about the predictability of hemostasis provided by BPAs, which is in agreement with the high proportion of untreated bleeds seen in the HAVEN 1 and 2 studies in PwHA with FVIII inhibitors compared with HAVEN 3, which was in PwHA without FVIII inhibitors. 25 The number of treated bleeds was low in PwHA both with or without FVIII inhibitors across both the major and minor procedures, suggesting that emicizumab provides hemostatic benefits for patients with or without FVIII inhibitors.…”
Section: Discussionmentioning
confidence: 93%
“…This may reflect concerns about the predictability of hemostasis provided by BPAs, which is in agreement with the high proportion of untreated bleeds seen in the HAVEN 1 and 2 studies in PwHA with FVIII inhibitors compared with HAVEN 3, which was in PwHA without FVIII inhibitors. 25 The number of treated bleeds was low in PwHA both with or without FVIII inhibitors across both the major and minor procedures, suggesting that emicizumab provides hemostatic benefits for patients with or without FVIII inhibitors.…”
Section: Discussionmentioning
confidence: 93%
“…While untreated bleeds may be a possibility in clinical practice depending on local protocols, 29 that should surely not be allowed to extend into clinical trials. It is good that a very recent report of data from a clinical trial of a non-CFC product has reported all joint bleeds and not just the treated ones.…”
Section: Reduction In Abr-treatment Efficacymentioning
confidence: 99%
“…Now consider a similar situation with joint bleeding. Fortunately, joint bleeding has a published definition, which was used in the HAVEN studies 5 . The 2014 ISTH guidelines define joint bleeding as a joint “aura” in combination with swelling/warmth, pain, and loss of range of motion of the joint, and note that improvement of symptoms with administration of clotting factor and rest can help distinguish arthropathy pain from bleeding 6 .…”
Section: Figurementioning
confidence: 99%
“…The HAVEN studies, 1 , 2 , 3 , 4 which have demonstrated the efficacy and safety of emicizumab, differed from most previous hemophilia studies not only in prophylaxis mechanism; they presented bleeding event data for both treated and untreated bleeds. In this issue of RPTH , Callaghan et al 5 present all available details of the untreated bleeds in HAVEN studies 1–3, including adults with HA and inhibitors (HAVEN 1), children with HA and inhibitors (HAVEN 2), and adults with HA without inhibitors (HAVEN 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation